Status and analysis of undetected plague cases in Yunnan Province, China - Su, Chao; Duan, Biao; Duan, Qun; He, Zhaokai; Sha, Hanyu; Liang, Yun; Pu, Ennian; Qin, Shuai; Duan, Ran; Lyu, Dongyue; Li, Wenbao; Tang, Deming; et al. (Frontiers in Public Health, 2024)
The virulence of Yersinia pestis strains in the Rattus flavipectus plague focus is relatively weak. The purpose of this study was to investigate the undetected, sporadic plague cases in plague foci and provide the basis for plague prevention and control.Methods: A 3-year-old plague-confirmed case was investigated in R. flavipectus plague focus of Yunnan Province in 2020 due to the intensive screening for fever symptoms during the COVID-19 epidemic. Epidemiological investigation, laboratory testing, and clinical treatment were conducted for the case. The expanded survey was carried out around the case within a 7-km radius, including the resident population, domesticated dogs, and rats. PCR and indirect hemagglutination tests were performed on the collected samples.The isolation rates of Y. pestis were 100.0% (7/7) in dead rats and 4.00%(3/75) in live rats in the survey area of the foci. And 5.00% (6/120) of the domesticated dogs were F1 antibody positive. Nine local people were detected for plague infection recently (0.92%, 9/978). The locations of human cases coincided with the Y. pestis epidemic area among the animals.This study discovered the existence of plague cases that had not been detected by routine surveillance in the R. flavipectus plague focus and the actual epidemic of human infection may be underestimated.